Inorganic Polyphosphate Amplifies High Mobility Group Box 1-Mediated Von Willebrand Factor Release and Platelet String Formation on Endothelial Cells - Biswas, Indranil; Panicker, Sumith R; Cai, Xiaofeng; Mehta-D'souza, Padmaja; Rezaie, Alireza R (Arteriosclerosis, thrombosis, and vascular biology, 2018)
Objective- Inorganic polyphosphate (polyP) is known to modulate coagulation, inflammation, and metabolic pathways. It also amplifies inflammatory responses of HMGB1 (high mobility group box 1) in endothelial cells. The objective of this study was to evaluate the effect of polyP on von Willebrand factor (VWF) release from endothelial cells with or without HMGB1. Approach and Results- EA.hy926 endothelial cells were treated with different concentrations of polyP alone or in combination with different concentrations of HMGB1. VWF release was measured by an ELISA assay in the absence or presence of pharmacological inhibitors of the receptor for advanced glycation end products, P2Y , and Ca . A flow chamber assay was used to monitor polyP -mediated platelet recruitment and VWF-platelet string formation. PolyP and HMGB1 induced VWF release from endothelial cells by a concentration-dependent manner. PolyP amplified HMGB1-mediated VWF release from endothelial cells. This was also true if boiled platelet releasate was used as the source of polyP. Gene silencing or pharmacological inhibitors of receptor for advanced glycation end products, P2Y , and Ca significantly inhibited VWF release. PolyP and HMGB1 synergistically promoted VWF-platelet string formation in the flow chamber assay, which was inhibited by the anti-GPIbα (glycoprotein Ib alpha) antibody. VWF release by polyP -HMGB1 complex required phosphorylation of Src and phospholipase C because inhibitors of Src, phospholipase C, and Ca signaling significantly decreased VWF secretion. The polyP -HMGB1 complex also increased angiopoietin-2 release, indicating that Weibel-Palade body exocytosis is involved in the VWF release. Conclusions- PolyP can promote thrombotic and inflammatory pathways by inducing VWF release and platelet string formation on endothelial cells.